2013
DOI: 10.1152/ajpheart.00498.2012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of site-specific phosphorylation of protein kinase A sites Ser23and Ser24of cardiac troponin I in human cardiomyocytes

Abstract: unphosphorylated, and cTnI-AA mimics both sites unphosphorylated. Force development was measured at various Ca 2ϩ concentrations in permeabilized cardiomyocytes in which the endogenous troponin complex was exchanged with these recombinant human troponin complexes. In donor cardiomyocytes, myofilament Ca 2ϩ sensitivity (pCa50) was significantly lower in cTnI-DD (pCa50: 5.39 Ϯ 0.01) compared with cTnI-AA (pCa50: 5.50 Ϯ 0.01), cTnI-AD (pCa50: 5.48 Ϯ 0.01), and cTnI-DA (pCa50: 5.51 Ϯ 0.01) at ϳ70% cTn exchange. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 53 publications
(122 reference statements)
10
66
3
Order By: Relevance
“…3, A and B). In addition, others have shown that ϳ50% cTnI phosphorylation is sufficient to induce a maximal response on myofilament calcium sensitivity (44). Fig.…”
Section: Impact Of Pka Treatment-mentioning
confidence: 94%
“…3, A and B). In addition, others have shown that ϳ50% cTnI phosphorylation is sufficient to induce a maximal response on myofilament calcium sensitivity (44). Fig.…”
Section: Impact Of Pka Treatment-mentioning
confidence: 94%
“…Phosphorylation of L-type calcium channels and phospholamban increases contractility by enhancing calcium influx and pumping into the sarcoplasmic reticulum 127 . Sarcomeric proteins are phosphorylated to enhance relaxation in the rapidly contracting heart: myosin binding protein C (MyBP-C) phosphorylation increases actin-myosin crossbridge kinetics [128][129][130] , titin phosphorylation decreases passive stiffness 131 and troponin I phosphorylation decreases calcium sensitivity 132,133 . Dephosphorylation of MyBP-C, titin and troponin I is observed in a wide range of cardiac diseases, including both heart failure with reduced ejection fraction and heart failure with preserved ejection fraction 134 , as well as hypertrophic cardiomyopathy 134 and dilated cardiomyopathy 135 , suggesting that this may be a common adaptation to increased mechanical strain.…”
Section: Box 2 | Physiological Modulations Of Sarcomeric Functionmentioning
confidence: 99%
“…Recombinant human troponin complex was produced as described in detail previously (39). Shortly, six different cardiac troponin I (cTnI) forms were made via site-directed mutations of Thr143 and Ser23/ Ser24 into aspartic acid (D) to mimic phosphorylation or into alanine (A) to mimic dephosphorylation: 143D, 143A, 23D/24D, 23D/24A, 23A/24D, and 23A/24A.…”
Section: Human Myocardial Tissuementioning
confidence: 99%
“…Exchange of recombinant cTn in human cardiomyocytes was done as described previously (39). Briefly, single cardiomyocytes were mechanically isolated with a glass tissue homogenizer and permeabilized by Triton X-100 (0.5%; v/v) for 5 min.…”
Section: Human Myocardial Tissuementioning
confidence: 99%
See 1 more Smart Citation